2017
DOI: 10.3390/biomimetics2020004
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Titanium(IV) Oxide onto 3D Spongin Scaffolds of Marine Sponge Origin According to Extreme Biomimetics Principles for Removal of C.I. Basic Blue 9

Abstract: Abstract:The aim of extreme biomimetics is to design a bridge between extreme biomineralization and bioinspired materials chemistry, where the basic principle is to exploit chemically and thermally stable, renewable biopolymers for the development of the next generation of biologically inspired advanced and functional composite materials. This study reports for the first time the use of proteinaceous spongin-based scaffolds isolated from marine demosponge Hippospongia communis as a three-dimensional (3D) templ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 70 publications
1
27
0
Order By: Relevance
“…Besides applications in the biomedical field, spongin-based scaffolds have been successfully used as adsorbents of diverse dyes [ 94 , 95 ] and as supports for enzyme immobilization [ 96 ]. It was recently shown that spongins are thermostable up to 260 °C [ 86 , 97 , 98 ]. This property opens the door for applications of spongin-based scaffolds with 3D architecture in such novel scientific disciplines as Extreme Biomimetics [ 99 ], with the aim of developing novel advanced composite materials.…”
Section: Spongins As Enigmatic Structural Proteins In Spongesmentioning
confidence: 99%
“…Besides applications in the biomedical field, spongin-based scaffolds have been successfully used as adsorbents of diverse dyes [ 94 , 95 ] and as supports for enzyme immobilization [ 96 ]. It was recently shown that spongins are thermostable up to 260 °C [ 86 , 97 , 98 ]. This property opens the door for applications of spongin-based scaffolds with 3D architecture in such novel scientific disciplines as Extreme Biomimetics [ 99 ], with the aim of developing novel advanced composite materials.…”
Section: Spongins As Enigmatic Structural Proteins In Spongesmentioning
confidence: 99%
“…These unique biopolymer-containing constructs offer alternative immobilization matrices that can be isolated from demosponges cultivated worldwide, to provide appropriate supports for a broad range of enzymes. Thus, demosponges of the order Dictioceratida (also known as commercial bath sponges) [7,8] represent a renewable source of proteinaceous spongin scaffolds which have recently been reported as effective in applications in extreme biomimetics [9][10][11][12], waste treatment [13][14][15][16][17], electrochemistry [18], and enzyme immobilization [19]. Meanwhile, marine demosponges of the order Verongiida have been recognized as a renewable source of uniquely pre-structured 3D chitinous scaffolds [20][21][22][23][24][25][26][27][28] which have found applications in tissue engineering [6,21,[29][30][31][32][33][34], drug release [35], the development of hybrid materials [36][37][38][39][40], and environmental science [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Broad diversity of secondary metabolites, mostly alkaloids and peptides, have been studied as potential antibacterial, antiviral, antifungal, and anticancer agents [9,10]. Biological materials such as structural collagenous proteinaceous spongin and aminopolysaccharide chitin have found applications in technology [3,11,12], extreme biomimetics [13][14][15][16][17][18], electrochemistry [19], and tissue engineering [20][21][22][23][24]. Thus, demosponges continue to be productive organisms for investigations of both marine pharmacology and biologically inspired materials science.…”
Section: Introductionmentioning
confidence: 99%